Colaborar - Ñamba'apo Oñondivepa - Collaboration: An Analysis of Inter-Agency Collaborations in Developmental Technical Assistance in Paraguay - Lindenbaum, Stephanie K (Tufts Archival Research Center, 2007)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: The United States Peace Corps has paired private American citizens with communities in developing countries for over forty years, yet it suffers a crisis of personality. Created ostensibly for the purpose of aiding developing world peoples, it is frequently criticized for providing a richer and more meaningful experience for the volunteers themselves than for their host communities. This paper examines Peace Corps' history and organizational culture as compared with the United States Agency for International Development, or USAID. With the Millennium Challenge Account threatening to alter the way in which USAID conducts development assistance programs abroad, it appears that USAID, like Peace Corps, should perhaps reevaluate its operations, and consider collaborating with other US Government agencies. Through two case studies of Peace Corps Volunteers in Paraguay, this paper looks at how they have worked on USAID-funded projects, and how this collaborative effort may be an attractive model for the future.